Mindfulness Communication to Improve Productivity: A Cross-Sectional Description of Female-Workers’ Opinions Through Qualitative-Focus-Groups - Ackerman, Lauren-Lee (The IIE, 2020)
This study gained an insightful perspective into how female employees feel about mindfulness communication and its role it plays in enhancing their productivity. This may/may not be helpful to a future company's goal of increasing their overall performance – before engaging in any policy training. This was a qualitative, descriptive study that made use of online focus-groups. This study thematically analysed and interpreted 6 female employee’s opinions on mindfulness communication and productivity. The findings showed that 35.3% of female employees felt if mindful communication were used by managers, this would positively affect their performance. Additionally, 23.53% felt that if mindfulness communication were not used, this would negatively affect their performance. Furthermore, 41,7% of female employees felt that if superiors used supportive communication this would increase their performance. While 20.8% felt that empathetic communication would increase productivity. Lastly, 37.5% felt that non-judgmental communication would improve their productivity.
Keywords: Mindfulness; Communication; Productivity; Opinions; Female workers